THE EFFECT OF PRODUCT QUALITY ON CONSUMER PURCHASE INTEREST WITH CUSTOMER SATISFACTION AS AN INTERVENING VARIABLE IN AUSTRALIAN MEDICAL AND HEALTH CARE STORE - Weihuan Zhau; Malvina Marchase (MEDALION JOURNAL: Medical Research, Nursing, Health and Midwife Participation, 2022)
This study aims to find out how the influence of product quality on consumer buying interest with customer satisfaction as an intervening variable at Australian Medical And Health Care Store. The research method used is the method of qualitative data and quantitative data. While the data used is primary data. The data analysis method in this study uses simple linear regression analysis to obtain a comprehensive picture of the influence of product quality variables on consumer buying interest using the SPSS 25 for Windows program. To find out whether there is a significant effect of the independent variable on the dependent variable, a simple linear regression model is used.